AlkTango reveals a role for Jeb/Alk signaling in the Drosophila heart - G Wolfstetter; T Masudi; E Uçkun; J Y Zhu; M Yi; V Anthonydhason; J Guan; H Sonnenberg; Z Han; R H Palmer (Cell Communication and Signaling)
Abstract Anaplastic lymphoma kinase (Alk) signaling is important in a variety of biological contexts such as cell type specification, regulation of metabolic and endocrine programs, behavior, and cancer. In this work, we generated a Tango GPCR assay-based, dimerization-sensitive Alk activity reporter (AlkTango) and followed receptor activation throughout Drosophila development. AlkTango reports Alk activation in embryonic and larval tissues previously linked to Alk signaling. Remarkably, AlkTango was active in the heart of Drosophila larvae and adult flies. We show that cardiomyocytes express Alk from late embryonic stages to adulthood, while jeb expression in pericardial cells coincided with AlkTango activity. Perturbation of cardiac Alk signaling leads to decreased adult survival as well as lower fitness and increased lethality in response to heat stress. In keeping with a role for Alk, heart measurements reveal arrythmia and irregular muscle contraction upon ligand stimulation. Finally, activation of cardiac Alk signaling induces hyperplasia in the accessory wing hearts of adult flies.